Training in multiple breath washout testing for respiratory physiotherapists. Issue 1 (March 2018) - O'Neill, Katherine; Elborn, J. Stuart; Tunney, Michael M.; O'Neill, Philip; Rowan, Stephen; Martin, Susan; Bradley, Judy M.
Abstract: Introduction: The development of multiple breath washout (MBW) testing in respiratory disease highlights the need for increased awareness amongst respiratory physiotherapists and a potential opportunity for professional development in the use of an important outcome measure for clinical trials. Objectives: To rationalise how MBW may be a useful assessment tool for respiratory physiotherapists and to describe a local MBW training and certification programme for physiotherapists. Results: The respiratory Multidisciplinary Team in the Belfast Health and Social Care Trust (BHSCT) identified a need for MBW testing to be available to facilitate clinical research and assessment. A 2 day training programme consisting of prereading preparation, self-directed learning, theory presentations, practical demonstrations and hands-on practice was developed and delivered. All participants underwent a certification process. Conclusion: We have demonstrated the successful training and certification of clinical and research physiotherapists and encourage other respiratory physiotherapists to consider MBW test training.